Land Acquisition Dispute in a National Strategic Project: the Case of Yogyakarta International Airport - Angga Prastyo Wibowo; Muhammad Zulfikar Amien (Fakultas Hukum Universitas Gadjah Mada, 2026)
This study analyzes the dynamics of land acquisition disputes to provide land for the construction of the so-called national strategic project, namely, the Yogyakarta International Airport (YIA). It also discusses the ratio decidendi of the administrative court at first instance and cassation levels, particularly in the context of legality and substantive justice. Previous studies have highlighted the role of the administrative court in land disputes, but few have examined changes in judges' opinions across levels. The object of examination is the Location Determination Permit (Izin Penetapan Lokasi, IPL) issued by the Governor. The first-instance court revoked the permit, but the Supreme Court overturned that decision. The results of the study show the importance of checks and balances mechanisms, transparency in public consultation, and active community participation in the development process. This study makes a new contribution by highlighting the integration of substantive justice into the practice of administrative justice, enabling national strategic projects to be carried out without sacrificing the rights and welfare of the community.